SPEECH FUNCTION ANALYSIS IN PRESIDENT PRABOWO SUBIANTO’ INTERVIEW WITH NAJWA SHIHAB - Natalia Murni Br Situmorang; Bertaria Sohnata Hutauruk; Melda Veby Ristella Munthe (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the speech functions used by President Prabowo Subianto and Najwa Shihab, particularly how the president conveys information and influences public perception. This study uses qualitative descriptive research, namely documentation analysis. Data were taken from the transcript of an interview between President Prabowo Subianto and Najwa Shihab during the